Self-propelled AzBA-algae microrobots enable rapid and stable dynamic remediation of sulfamethoxazole in aqueous environments - Jinxin Liu; Lin Cheng; Han Fu; Zhili Gao; Junjie Li; Jiawei He; Cheng Tian; Shusheng Zhang (Bioresource Technology, 2026)

3D-printed Li-HA composite scaffold with staged simvastatin/NGF delivery and continuous Li+ signaling enhances immune–neuro–angiogenic coupling for bone repair - Xianglei Mo; Tengbin Shi; Siyi Huang; Dongyi Mai; Lingyu Kong; Junkai Mi; Zongqiang Gao; Wenge Liu; Yanjin Lu; Tingting Huang; Jinxin Lin (Chemical Engineering Journal, 2026)

Heavy-metal and nutrient enrichment triggered a regime shift in marsh diatom assemblages over the past millennium - Dongxue Han; Jinxin Cong; Lin Li; Guoping Wang; Chuanyu Gao (Journal of Environmental Management, 2026)

Co NPs@N-Doped Peanut Shell-derived Biochar As an Efficient Catalyst for Peroxymonosulfate Activation in Acetaminophen Degradation - Xiaoxin Chen; Xingzi Zhu; Caiyan Ge; Jinxin Wang; Manli Guo; Yujuan Cao; Bixia Lin (Water, Air, & Soil Pollution, 2026)

Improving consistency of WRF-UCM-based typhoon wind field simulations with field observations: A sensitivity analysis of model parameters - Yuxin Zhang; Qiusheng Li; Shuyang Cao; Junyi He; P.W. Chan; Lin Zhao; Jinxin Cao (Urban Climate, 2026)

Room-temperature covalent organic polymers with hydroxyl engineering for ultra-high polychlorinated biphenyls uptake - Feifei Lu; Xinglin Wu; Jinxin Chi; Biao Huang; Fahui Xiang; Yonghui Lin; Xucong Lin (Analytica Chimica Acta, 2026)

Design, preparation and application of triboelectric energy harvester with antibacterial performances - Changmei Lin; Zhenhao Pei; Jinxin Lan; Jianhui Huang; Minghua Liu; Shilin Cao; Xiaojuan Ma (Chemical Engineering Journal, 2025)

The effect of construction measures on the seismic performance of a frame-infilled wall with fabricated constructional column - Shucheng Yuan; Haifeng Lin; Haibo Luo; Zhanyuan Zhu; Zuyin Zou; Wei Liang; Zhuoying Wang; Bing Ma; Jinxin Yao; Qichao Zhang; Jiangfeng Dong; Hwa Kian Chai (Bulletin of Earthquake Engineering, 2025)

Multi-target-responsive AIE material for in situ visualization of level 3 features in latent fingerprints - Guoxin Zhuang; Jinxin Wei; Yonglin Wen; Yujing Li; Youpeng Xu; Yisheng Jiang; Xianghui Lai; Liang Meng; Zhiyu Liang; Xiaohui Lin; Lijun Ma; Guosong Lin; et al. (Analytica Chimica Acta, 2025)

A knowledge-guided LSTM reservoir outflow model and its application to streamflow simulation in reservoir-regulated basins - Runting Chen; Dagang Wang; Yiwen Mei; Yongen Lin; Zequn Lin; Zhi Zhang; Shengjie Zhuang; Jinxin Zhu; Jonghun Kam; Yiping Wu; Guoping Tang (Journal of Hydrology, 2025)

Copper doped carbon dots for selective determination of regulated aniline additives and safe hair dyeing - Zhanghong Guo; Lin Zhou; Liping Zhang; Haining Cui; Jinxin Ma; Chan Wang; Qijun Song (Analytica Chimica Acta, 2025)

Molecular and pharmacological characterization of the dopamine receptors in the oriental fruit fly, Bactrocera dorsalis - Shiyan Liu; Xuefeng Zhang; Xin Gong; Jinxin Yu; Tao Lin; Qian Xiang; Xinnian Zeng; Jiali Liu (Insect Biochemistry and Molecular Biology, 2025)

Characterization of two novel angiotensin converting enzyme-inhibitory peptides from yellow tuna peptides: Inhibitory mechanism, transport route and network pharmacology analysis - Jinxin Wang; Si-jie Guo; Xing Xie; Tian-xin Ma; Qin-hui Wen; Yong-lin Gao; Yueming Li; Jian Zhang; Wenjun Li; Lu Zhang (Food Research International, 2025)

Experimental Study of the Hydrodynamic Forces of Pontoon Raft Aquaculture Facilities Around a Wind Farm Monopile Under Wave Conditions - Deming Chen; Mingchen Lin; Jinxin Zhou; Yanli Tang; Fenfang Zhao; Xinxin Wang; Mengjie Yu; Qiao Li; Daisuke Kitazawa (Journal of Marine Science and Engineering, 2025)
The integrated development of offshore wind power and marine aquaculture represents a promising approach to the sustainable utilization of ocean resources. The present study investigated the hydrodynamic response of an innovative combination of a wind farm monopile and pontoon raft aquaculture facilities (PRAFs). Physical water tank experiments were conducted on PRAFs deployed around a wind farm monopile using the following configurations: single- and three-row arrangements of PRAFs with and without a monopile. The interaction between the aquaculture structure and the wind farm monopile was examined, with a particular focus on the mooring line tensions and bridle line tensions under different wave conditions. Utilizing the wind farm monopile foundation as an anchor, the mooring line tension was reduced significantly by 16–66% in the single-row PRAF. The multi-row PRAF arrangement experienced lower mooring line tension in comparison with the single-row PRAF arrangement, with the highest reduction of 73%. However, for the bridle line tension, the upstream component was enhanced, while the downstream one was weakened with a monopile, and they both decreased in the multi-row arrangement. Finally, we developed numerical models based on flume tank tests that examined the interactions between the monopile and PRAFs, including configurations of a single monopile, along with single- and three-row arrangements of PRAFs. The numerical simulation results confirmed that the monopile had a dampening effect on the wave propagation of 5% to 20%, and the impact of the pontoons on the monopile was negligible, implying that the integration of aquaculture facilities around wind farm infrastructure may not significantly alter the hydrodynamic loads experienced by the monopile.

Mussel-inspired integrated functional 3D printed scaffolds with molybdenum disulfide nanoflowers for tumor therapy and bone reconstruction - Lan Li; Rongcan Wu; Ruchen Hong; Xiaolong Chen; Tingting Huang; Siyi Huang; Xianglei Mo; Zhiyi Wang; Wenge Liu; Yanjin Lu; Ye Wu; Jinxin Lin (Chemical Engineering Journal, 2025)

Reducing defects in hard carbon graphite domain: Employing a fully dynamic bonding with a multi-crosslinked biomass-based binder for enhanced sodium ion storage - Jiaqi Jiao; Han Lu; Conghua Yi; Dongjie Yang; Xuezhi Zeng; Jinxin Lin; Hongqiang Li (Chemical Engineering Journal, 2024)

Magnetic bio-based Fe3O4@urushiol-Fe polymeric nanoparticles for efficient photothermal sterilization - Weibin Bai; Xu Zhang; Xinghang Chen; Pengcheng Li; Jinxin Huang; Jiani Chen; Shijing Zheng; Xiaoyan Li; Yucai Lin; Rongkun Jian (Journal of Environmental Chemical Engineering, 2024)

Enhancing plant fiber antibacterial and antiviral performance through synergistic action of amino and sulfonic acid groups - Jinxin Lan; Yao Wu; Jiazhen Chen; Peng Wang; Hui Chen; Jinfeng Huang; Dongdong Lu; Changmei Lin; Xiaojuan Ma; Shilin Cao (Carbohydrate Polymers, 2024)

Quantifying Post-peak Behavior of Rocks with Type-I, Type-II, and Mixed Fractures by Developing a Quasi-State-Based Peridynamics - Feng Tian; Zaobao Liu; Jinxin Zhou; Lin Chen; Xia-ting Feng (Rock Mechanics and Rock Engineering, 2024)

Incorporating physiological knowledge into correlative species distribution models minimizes bias introduced by the choice of calibration area - Zhixin Zhang; Jinxin Zhou; Jorge García Molinos; Stefano Mammola; Ákos Bede-Fazekas; Xiao Feng; Daisuke Kitazawa; Jorge Assis; Tianlong Qiu; Qiang Lin (Marine Life Science & Technology, 2024)
Correlative species distribution models (SDMs) are important tools to estimate species’ geographic distribution across space and time, but their reliability heavily relies on the availability and quality of occurrence data. Estimations can be biased when occurrences do not fully represent the environmental requirement of a species. We tested to what extent species’ physiological knowledge might influence SDM estimations. Focusing on the Japanese sea cucumber Apostichopus japonicus within the coastal ocean of East Asia, we compiled a comprehensive dataset of occurrence records. We then explored the importance of incorporating physiological knowledge into SDMs by calibrating two types of correlative SDMs: a naïve model that solely depends on environmental correlates, and a physiologically informed model that further incorporates physiological information as priors. We further tested the models’ sensitivity to calibration area choices by fitting them with different buffered areas around known presences. Compared with naïve models, the physiologically informed models successfully captured the negative influence of high temperature on A. japonicus and were less sensitive to the choice of calibration area. The naïve models resulted in more optimistic prediction of the changes of potential distributions under climate change (i.e., larger range expansion and less contraction) than the physiologically informed models. Our findings highlight benefits from incorporating physiological information into correlative SDMs, namely mitigating the uncertainties associated with the choice of calibration area. Given these promising features, we encourage future SDM studies to consider species physiological information where available.

Association between per- and polyfluoroalkyl substances exposure and prevalence of chronic obstructive pulmonary disease: The mediating role of serum albumin - Yan Wang; Jingwen Zhang; Jiaxian Zhang; Miao Hou; Lingkun Kong; Xiong Lin; Jinxin Xu; Chun Yan; Fan Lin; Sunkui Ke (Science of The Total Environment, 2024)

STON2 variations are involved in synaptic dysfunction and schizophrenia-like behaviors by regulating Syt1 trafficking - Yuanlin Ma; Kai Gao; Xiaoxuan Sun; Jinxin Wang; Yang Yang; Jianying Wu; Anping Chai; Li Yao; Nan Liu; Hao Yu; Yi Su; Tianlan Lu; et al. (Science Bulletin, 2024)

A novel model for sustainable production scheduling of an open-pit mining complex considering waste encapsulation - Jingsi Lin; Mohammad Waqar Ali Asad; Erkan Topal; Ping Chang; Jinxin Huang; Wei Lin (Resources Policy, 2024)

Considering biotic interactions exacerbates the predicted impacts of climate change on coral‐dwelling species - Zhixin Zhang; Shaobo Ma; Ákos Bede‐Fazekas; Stefano Mammola; Meng Qu; Jinxin Zhou; Ellias Yuming Feng; Geng Qin; Qiang Lin (Journal of Biogeography, 2024)
Aim Climate change is affecting the geographic distributions of many species and researchers are increasingly relying on species distribution models (SDMs) to forecast species' redistributions under climate change. Such modelling studies, however, often ignore biotic interactions that shape species' geographic ranges. This is especially problematic for coral reefs, which host a high diversity of species and interactions. We tested how biotic interactions affect the distribution patterns of obligate coral‐dwelling Trapezia crabs. Location Global coastal ocean. Time Period 2000–2014, 2040–2050, 2090–2100. Major Taxa Studied Corals and coral‐dwelling Trapezia crabs. Methods We determined the symbiotic relationships between 22 crab species in the genus Trapezia and corals via field survey and extensive literature review. We first developed SDMs for coral and crab species using exclusively abiotic variables (abiotic‐only models for corals and crabs). Then we constructed a second set of models where we accounted for coral distributions into crab predictions by combining model predictions for the two taxa a posteriori (abiotic‐plus‐biotic models for crabs only). Results We obtained 30 commonly accepted coral‐crab symbiotic relationships from nine Trapezia crab and six stony coral species. The abiotic‐only model predictions showed that six corals may lose approximately one‐sixth of suitable ranges under RCP 8.5 in 2040–2050. The two types of models for crabs yielded largely different habitat suitability predictions and accounting for biotic interactions into SDM predictions exacerbates the predicted impacts of climate change on coral‐dwelling crabs. Main Conclusions Our results show large discrepancies in crab spatial distribution patterns with and without accounting for symbiotic interactions. Our findings highlight the important role of modeller's decision on accounting for biotic interactions when predicting the geographical ranges of coral‐dwelling species, with important implications for designing future conservation and management strategies for marine species.

Development of objective function-based ensemble model for streamflow forecasts - Yongen Lin; Dagang Wang; Jinxin Zhu; Wei Sun; Chaopeng Shen; Wei Shangguan (Journal of Hydrology, 2024)

Association of the cloud radiative effect with the changes in the northern edge of Hadley circulation between the CMIP5 and CMIP6 models in boreal summer - Shu Gui; Ruowen Yang; Chuanfeng Zhao; Lin Wang; Jinxin Cheng; Ning Qi; Huan Yang (Theoretical and Applied Climatology, 2024)

Conversion of highly polymerized lignin into monophenolic products via pyrolysis: A comparative study of acidic and alkaline depolymerization pretreatments using deep eutectic solvents - Xin Yue; Jinxin Lin; Terhi Suopajärvi; Otto Mankinen; Atte Mikkelson; Rui Liu; Harri Huttunen; Liheng Chen; Chunlin Xu; Ville-Veikko Telkki; Shirong Sun; Henrikki Liimatainen (Chemical Engineering Journal, 2023)

A strong high-temperature event in late-spring 2023 in Yunnan province, Southwest China: Characteristics and possible causes - Zizhen Dong; Ruowen Yang; Jie Cao; Lin Wang; Jinxin Cheng (Atmospheric Research, 2023)

Green hydrogen production and liquefaction using offshore wind power, liquid air, and LNG cold energy - Xiaoyuan Chen; Jinxin Yue; Lin Fu; Mingshun Zhang; Miangang Tang; Juan Feng; Boyang Shen (Journal of Cleaner Production, 2023)

Adding the third component with similar building blocks to regulate the miscibility of active layer enables high efficient ternary solar cells - Shichu Peng; Jinxin Luo; Peng Li; Liangang Xiao; Chongqing Yang; Yaocheng Jin; Ruiying Lin; Yanping Huo; Yi Liu; Yonggang Min (Chemical Engineering Journal, 2023)

Insight into the selective oxidation behavior of organic pollutants via Ni-N4-C mediated electron transfer pathway - Huchuan Yan; Cui Lai; Shiyu Liu; Dongbo Wang; Xuerong Zhou; Mingming Zhang; Ling Li; Dengsheng Ma; Fuhang Xu; Xiuqin Huo; Lin Tang; Ming Yan; et al. (Chemical Engineering Journal, 2023)

Study on Tamped Spherical Detonation-Induced Dynamic Responses of Rock and PMMA Through Mini-chemical Explosion Tests and a Four-Dimensional Lattice Spring Model - Jianjun Ma; Jinxin Zhao; Yuexiang Lin; Jiguan Liang; Junjie Chen; Wanxiang Chen; Linchong Huang (Rock Mechanics and Rock Engineering, 2023)

Transcriptomic analysis the mechanisms of anti-osteoporosis of desert-living Cistanche herb in ovariectomized rats of postmenopausal osteoporosis - Shuo Tian; Lin Guo; Yagang Song; Jinxin Miao; Mengfan Peng; Xiaoyan Fang; Ming Bai; Mingsan Miao (Functional & Integrative Genomics, 2023)

Totally-green cellulosic fiber with prominent sustained antibacterial and antiviral properties for potential use in spunlaced non-woven fabric production - Jinxin Lan; Yao Wu; Changmei Lin; Jiazhen Chen; Ruiqi Zhu; Xiaojuan Ma; Shilin Cao (Chemical Engineering Journal, 2023)

Human umbilical cord mesenchymal stem cell-derived exosomes carrying miR-1827 downregulate SUCNR1 to inhibit macrophage M2 polarization and prevent colorectal liver metastasis - Jierong Chen; Ziyue Li; Caifeng Yue; Jianhong Ma; Lixue Cao; Jiaxin Lin; Dandan Zhu; Ran An; Jinxin Lai; Yunmiao Guo; Bing Gu (Apoptosis, 2023)

Exploring the abundance and influencing factors of antimicrobial resistance genes in manure plasmidome from swine farms - Zunfang Tu; Junrui Shui; Jinxin Liu; Hongmei Tuo; Haoyu Zhang; Cong Lin; Jingyi Feng; Yuxuan Feng; Wen Su; Anyun Zhang (Journal of Environmental Sciences, 2023)

Insights into the fates of plasmids and antimicrobial resistance genes during swine manure treatment and related factors based on plasmidome and metagenome analyses - Junrui Shui; Hongmei Tuo; Jinxin Liu; Xialan Zhang; Jingyi Feng; Yuxuan Feng; Wen Su; Cong Lin; Haoyu Zhang; Zunfang Tu; Hongning Wang; Anyun Zhang (Environmental Science and Pollution Research, 2022)

Comprehensive identification of protein orthologs in the family Ascoviridae facilitates an understanding of phylogenomics, protein conservation, and phosphorylation - Yanhua Shi; Weiping Lin; Jinxin Chu; Guohui Wang; Punan Zhao; Guo-hua Huang; Dianhai Hou (Archives of Virology, 2022)

Identification of a novel bocaparvovirus in a wild squirrel in Kunming, Yunnan Province, China - Jiali Wang; Nan Li; Zhao Li; Lin Liu; Yuwen He; Jinxin Meng; Shunxiang Li; Jinglin Wang (Archives of Virology, 2020)

Characterization of Eptesipoxvirus, a novel poxvirus from a microchiropteran bat - Shin-Lin Tu; Yoshinori Nakazawa; Jinxin Gao; Kimberly Wilkins; Nadia Gallardo-Romero; Yu Li; Ginny L. Emerson; Darin S. Carroll; Chris Upton (Virus Genes, 2017)